(untitled) (Research, Society and Development, 2022)
This article sought to develop a botanical guide in Libras with the divisions of the Plantae Kingdom in order to facilitate the teaching and learning process of deaf and hearing students, enabling their understanding of the proposed theme. It is important to point out the lack of teaching materials regarding the teaching of Science and Biology, so this work is justified due to the absence of these materials for the teaching of these students. The illustrative guide presented provides content that arouses the student’s curiosity, has attractive illustrations, the signs presented are easy to interpret, easy to handle, of good quality and the visual presentation is pleasant for the intended age group. It is concluded that the construction of this didactic guide is an important tool to facilitate and assist in the teaching and learning process of the deaf student, also serving the hearing student. It is evident that this work collaborates with more works directed to the area.